P712 Tofacitinib efficacy in patients with moderate to severe ulcerative colitis: Subgroup analyses of OCTAVE Induction 1 and 2 and OCTAVE Sustain by 5-aminosalicylates use. (25th January 2019) - Hanauer, S; Rubin, D T; Gionchetti, P; Su, C; Woodworth, D A; Quirk, D; Salese, L; Wang, W; Marren, A; Lawendy, N; Panaccione, R
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). The efficacy and safety of tofacitinib were demonstrated in three Phase 3 trials (OCTAVE Induction 1 and 2, NCT01465763 and NCT01458951; OCTAVE Sustain, NCT01458574) in patients with moderate to severe UC [1]. In this post-hoc analysis, we explored tofacitinib efficacy for patients with (c5-ASA) and without (n5-ASA) concomitant 5-aminosalicylates use. Methods: In OCTAVE Induction 1 and 2, patients received placebo or tofacitinib 10 mg twice daily (BID) for 8 weeks; clinical responders were re-randomised into OCTAVE Sustain for 52 weeks and received placebo, tofacitinib 5 or 10 mg BID. c5-ASA were permitted at entry, provided doses were stable ≥4 weeks prior to and during the trials. Remission and mucosal healing were summarised at Week 8 (OCTAVE Induction 1 and 2) and Week 52 (OCTAVE Sustain) by c5-ASA status. Generalised linear models were used to compare the adjusted treatment effects between 5-ASA subgroups (Tables 1 and 2). Results: A smaller proportion of c5-ASA patients had prior tumour necrosis factor inhibitor (TNFi) and immunosuppressant failure compared with n5-ASA patients, at baseline of OCTAVE Induction and Sustain (OCTAVE Induction 1 and 2: TNFi failure 42.7% vs. 74.5%; immunosuppressant failure 69.4% vs. 78.3%; OCTAVE Sustain: TNFi failure 36% vs. 70%; immunosuppressant failure 67.9% vs. 80%). For both c5-ASA and n5-ASA subgroups, a higher proportion of tofacitinib-treated patients achieved efficacy endpoints, compared with placebo-treated patients, at Week 8 of OCTAVE Induction 1 and 2 and Week 52 of OCTAVE Sustain (Tables 1 and 2). Without controlling for baseline variables, higher treatment effects were observed within the c5-ASA subgroup compared with the n5-ASA subgroup; however, when controlled for prior TNFi and immunosuppressant failure (and baseline remission status in OCTAVE Sustain), the differences were not statistically significant in treatment effects between the 5-ASA subgroups in terms of adjusted odds ratios (Tables 1 and 2). Conclusions: When controlling for prior UC treatment status, efficacy of tofacitinib, based on adjusted odds ratios, was similar regardless of 5-ASA status. This analysis is limited by subgroup size differences. References 1. Sandborn WJ, Su C, Sands BE, et al. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2017;376:1723–36.